2021
DOI: 10.3390/molecules26216658
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Silico Studies, and Evaluation of Syn and Anti Isomers of N-Substituted Indole-3-carbaldehyde Oxime Derivatives as Urease Inhibitors against Helicobacter pylori

Abstract: Gastrointestinal tract infection caused by Helicobacter pylori is a common virulent disease found worldwide, and the infection rate is much higher in developing countries than in developed ones. In the pathogenesis of H. pylori in the gastrointestinal tract, the secretion of the urease enzyme plays a major role. Therefore, inhibition of urease is a better approach against H. pylori infection. In the present study, a series of syn and anti isomers of N-substituted indole-3-carbaldehyde oxime derivatives was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, two absorption bands at 3331 -3427 cm À 1 and 3110 -3214 cm À 1 related to the NÀ H bonds. 1 H-NMR spectra of the ureide two singlet peaks exhibited NÀ H bonds at 9.85 -9.88 and 8.30 -8.31 ppm; the triazolyl hydrogen showed a peak at 7.25 -7.53 ppm and a peak at 5.08 -5.13 ppm related to the C4 proton of the THPM ring. As the 1 H-NMR spectrum of compound 9a, the ureide NHs were characterized at δ 9.88 and δ 8.31 as two singlet peaks.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, two absorption bands at 3331 -3427 cm À 1 and 3110 -3214 cm À 1 related to the NÀ H bonds. 1 H-NMR spectra of the ureide two singlet peaks exhibited NÀ H bonds at 9.85 -9.88 and 8.30 -8.31 ppm; the triazolyl hydrogen showed a peak at 7.25 -7.53 ppm and a peak at 5.08 -5.13 ppm related to the C4 proton of the THPM ring. As the 1 H-NMR spectrum of compound 9a, the ureide NHs were characterized at δ 9.88 and δ 8.31 as two singlet peaks.…”
Section: Chemistrymentioning
confidence: 99%
“…Nevertheless, it is identified that most stomachassociated infections are triggered by a Gramnegative bacterium recognized as the Helicobacter pylori (H. pylori), which is frequently known for its high level of urease activity. [1] H. pylori is assessed to be colonizing the stomach, beginning an extensive spectrum of diseases ranging from gastritis and gastric ulcers to stomach cancer. More than 90 % of the cases of gastric cancer, the third most common cause of cancer death worldwide, are related to the chronic H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitors of the urease can be categorized into two classes; substrate like inhibitors (hydroxyurea, hydroxamic acids) and mechanism based inhibitors (phosphorodiamidates). During the past years, extensive research has been done on the design and development of urease inhibitors such as hydroxamic acids, [51] urea and thiourea derivatives, [52] polyphenols, [53] isoniazids, [54] catechol-based inhibitors, [55] flavonoids, [56] coumarins, [57] indoles, [58] chalcones, [59] thiazoles, [60] thiazolidinones, [61] benzothiazoles, [62] benzoxazoles, [63] benzimidazoles, [64] barbituric acid and thiobarbituric acid derivatives, [65] quinazolinones, [66] triazoles, [67] phosphoramides, [68] sulfonamides, [69] thiadiazoles, [70] oxadiazoles, [71] thiosemicarbazones, [72] diamides, [73] benzenesulfonohydrazides [74] and many more. The most effec-tive inhibitors of urease cited in the literature are phosphorodiamide and phosphorotriamide derivatives such as NBPT (N-n butylthiophosphorictriamide), PPD (phenylphosphorodiamidate), NBPTO (N-n butylphosphorictriamide and flurofamide (Ndiaminophosphoryl-4-fluorobenzamide) [75] (Figure 6).…”
Section: Inhibitors Of Ureasementioning
confidence: 99%
“…[30][31][32] Dinuclear transition metal compounds play prominent roles in electron transfer processes in metallobiomolecules, [33][34][35][36][37] which can be confirmed by citing an example of a unique representation of a heteroleptic paddlewheel complex of nickel(II) that has been synthesized and structurally characterized. 38 Extensive research has been dedicated to the synthesis of dinuclear metal compounds that mimic several metallobiomolecules like urease [39][40][41] and catecholase. [42][43][44] Dinuclear nickel(II) compounds have been known to catalyze catechol oxidation.…”
Section: Introductionmentioning
confidence: 99%